DOACs or VKAs or LMWH – What is the optimal regimen for cancer-associated venous thromboembolism? A systematic review and meta-analysis. (July 2022) - Yamani, Naser; Unzek, Samuel; Almas, Talal; Musheer, Adeena; Ejaz, Arooba; Paracha, Anousheh Awais; Shahid, Izza; Mookadam, Farouk
Abstract: Background: Clinical guidelines have supported the use of direct anticoagulants (DOACs) for the treatment of cancer-associated venous thromboembolism (Ca-VTE). However, recent trials have reported increased bleeding risks associated with DOACs usage, raising concerns regarding its efficacy. Objectives: The authors conducted a meta-analysis to study the efficacy and safety of DOACs for the treatment of VTE in cancer patients, compared with Low-weight molecular heparin (LMWH) and Vitamin-K antagonists (VKAs). Methods: PubMed, EMBASE, Cochrane Library, Cochrane Central Register of Controlled Trials (CENTRAL) were searched according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines from inception to June 17th, 2021.The primary outcomes studied were VTE recurrence and major bleeding. Results: A total of 8 randomized controlled trials (RCTs) enrolling almost 7000 patients were included. Direct oral anticoagulants significantly reduced VTE Recurrence in cancer patients when compared to patients treated with LMWH or VKAs (Hazard ratio [HR] 0.62, 95% confidence interval [CI] 0.46–0.83; P = 0.002; I 2  = 26%). There were no statistically significant differences for major bleeding (HR 0.86, 95% confidence interval [CI] 0.56–1.33; P = 0.50; I 2  = 34%), clinically relevant non-major bleeding (HR 1.23, 95% confidence interval [CI] 0.79–1.91; P = 0.35; I 2  = 66%), pulmonary embolism (HR 0.71, 95% confidence interval [CI] 0.47–1.06; P = 0.10; I 2  = 7%), and all-cause mortality (HR 0.98, 95% confidence interval [CI] 0.86–1.12; P = 0.78; I 2  = 1%), between DOACs and LMWH. Conclusion: This analysis shows that DOACs are the optimal regimen to treat Ca-VTE. They have a similar to slightly increased bleeding risk compared with LMWH and are a safer alternative to VKAs. Graphical abstract: Image 1 Highlights: Patients receiving DOACs show a significant decrease for VTE recurrence. Rivaroxaban pertaining to the most effective DOAC. Edoxaban proving to be more useful in reducing bleeding risk more than LMWHs. Further research is needed to investigate the correlation between cancer types and the efficacy of DOACs in treating Ca-VTE.